Do sertão ao asfalto, das páginas para as telas: identidade e representação das personagens nordestinas em Vidas secas e A hora da estrela - Aragão, Gleyda Lucia Cordeiro Costa (2019)
This research has as main objective to analyze the construction of the Northeast characters in the books Vidas Secas (1938), of Graciliano Ramos and A hora da estrela (1977), of Clarice Lispector, as well as their respective adaptations for the cinema. We will investigate the strategies used by the directors (Nelson Pereira dos Santos and Suzana Amaral) and their teams in the presentation of the characters Fabiano, Sinhá Vitória, Macabéa and Olímpico, focusing mainly on the constitution of the identity of these beings, as well as the representation of the Northeast in these productions. We start from the idea that often this region and its inhabitants are presented in stereotyped form in several artistic productions, which contributes to a misrepresented image of both. In this way, we conclude that Nelson Pereira dos Santos and Suzana Amaral constructed narratives very close to those of the texts of departure, adding elements that corroborated with the picture presented by the writers. All the elements of complaint in the texts remained in the films. They have shown that even though decades have passed between the writing of books and the making of films, certain retrograde and unabashed aspects of our social relations still survive. Thus, it is evident that the backward, primitive and retrograde is not the Northeast or the Northeast, but the power relations that have established themselves in the country. In the specific case of this region, the drought only serves as a smoke screen to legitimize certain deviations. As a theoretical contribution, we are based on the concepts of adaptation of Hutcheon (2013), film adaptation of Cattrysse (1992) and Stam (2006) and rewriting of Lefevere (1992). In addressing the concepts of identity and representation, we used the writings of Hall (2002, 2006), Bauman (2005, 2011), Albuquerque Jr. (2007, 2009).This research has as main objective to analyze the construction of the Northeast characters in the books Vidas Secas (1938), of Graciliano Ramos and A hora da estrela (1977), of Clarice Lispector, as well as their respective adaptations for the cinema. We will investigate the strategies used by the directors (Nelson Pereira dos Santos and Suzana Amaral) and their teams in the presentation of the characters Fabiano, Sinhá Vitória, Macabéa and Olímpico, focusing mainly on the constitution of the identity of these beings, as well as the representation of the Northeast in these productions. We start from the idea that often this region and its inhabitants are presented in stereotyped form in several artistic productions, which contributes to a misrepresented image of both. In this way, we conclude that Nelson Pereira dos Santos and Suzana Amaral constructed narratives very close to those of the texts of departure, adding elements that corroborated with the picture presented by the writers. All the elements of complaint in the texts remained in the films. They have shown that even though decades have passed between the writing of books and the making of films, certain retrograde and unabashed aspects of our social relations still survive. Thus, it is evident that the backward, primitive and retrograde is not the Northeast or the Northeast, but the power relations that have established themselves in the country. In the specific case of this region, the drought only serves as a smoke screen to legitimize certain deviations. As a theoretical contribution, we are based on the concepts of adaptation of Hutcheon (2013), film adaptation of Cattrysse (1992) and Stam (2006) and rewriting of Lefevere (1992). In addressing the concepts of identity and representation, we used the writings of Hall (2002, 2006), Bauman (2005, 2011), Albuquerque Jr. (2007, 2009).